Nanotechnology-Enabled Niosomal Nasal Sprays: Unlocking New Therapeutic Avenues for Alzheimer’s Disease - Charde Yugali,; Dhapake Pankaj,; Dhoble Nilakshi,; Padole Nitin,; Baheti Jagdish, (Asian Journal of Pharmaceutical Research and Development, 2026)
To determine the viability of using niosome-based nasal sprays as a new delivery method for therapeutic use in Alzheimer’s disease. Through searches of current peer-reviewed publication materials through study of nanotechnology drug delivery systems, intranasal delivery and therapeutics used in the treatment of Alzheimer’s. Relevance to niosomal formulations, pathway of nose-to-brain administration and previous or ongoing studies (preclinical)/clinical studies on therapeutics developed to treat Alzheimer’s.Alzheimer’s is a progressive neurodegenerative disorder with limited options for therapy, due largely to the inability of drug molecules to effectively pass through the blood-brain barrier (BBB). Intranasal administration provides non-invasive delivery of therapeutics, eliminating the need for crossing through the BBB (via olfactory/trigeminal nerves). Niosomes formulated from non-ionic surfactants and cholesterol provide improved stability, bioavailability and sustained-release of active ingredients. Niosomal form would improve delivery of therapeutics into the brain, decrease the incidence of systemic adverse effects from drugs used to treat Alzheimer’s and enhance therapeutic effectiveness in an Alzheimer’s patient. Preliminary clinical trials for the use of niosomes demonstrate improved pharmacokinetics of the drug, cognitive improvement for patients receiving niosomal therapy and greater safety of niosomal therapies over traditionally formulated products.The use of niosomal nasal sprays for the targeted administration (i.e., brain) of therapeutics for treating Alzheimer’s represents a powerful and innovative approach to address Alzheimer’s disease and will require additional clinical evidence and methods to support large-scale niosome production.